2019
DOI: 10.5530/jyp.2019.11.56
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perspectives on Services Provided by Community Pharmacies in Terms of Patients’ Perception and Satisfaction

Abstract: Objective: To assess patients' perspectives towards community pharmacists as health care professionals by evaluating their performance in terms of patients' perception and satisfaction. Methods: Patients' perception and satisfaction are widely used healthcare direct pointers to evaluate Pharmaceutical health care services. To examine these two parameters, a questionnaire was developed, including statements to assess the patients' level of compatibility towards their community pharmaceutical care settings, alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Therefore, pharmacists need to fully practice their role for the benefit of their patients (El-Sharif et al 2017). Another study in the UAE was also conducted by Saad Ali et al, (2019) reported that 72.8% of patients were very satisfied with simple, understandable language used by the pharmacists. However, the patients were not satisfied with the privacy while pharmacists discussed with patients (Saad Ali et al 2019).…”
Section: Patient Satisfaction With Pharmaceutical Care Servicesmentioning
confidence: 99%
“…Therefore, pharmacists need to fully practice their role for the benefit of their patients (El-Sharif et al 2017). Another study in the UAE was also conducted by Saad Ali et al, (2019) reported that 72.8% of patients were very satisfied with simple, understandable language used by the pharmacists. However, the patients were not satisfied with the privacy while pharmacists discussed with patients (Saad Ali et al 2019).…”
Section: Patient Satisfaction With Pharmaceutical Care Servicesmentioning
confidence: 99%
“…For instance, more than 30% of participants in 11 studies considered pharmacists as business people or mere vendors/dispensers of medications. 31,37,39,44,46,51,53,55,57,60,61,63 Expectations of pharmacist duties included treatment of minor health ailments, consultation on over-the-counter medications and parapharmaceutical products, and accuracy checking of dispensed medications. For instance, over 60% of participants in 5 studies expected the pharmacist to treat minor illnesses.…”
Section: Attitudes Towards Community Pharmacist Rolementioning
confidence: 99%
“…39,40,44,54,55 Another expected task was medication counseling with over 70% of participants in 6 studies agreeing that the pharmacist should provide counseling directions on medication use. 39,40,[52][53][54]63 Conducting screening for specific health conditions or diseases including hypertension and diabetes and monitoring or following up patient progress were not common The public views of the community pharmacy services currently provided in Qatar/(SA&A**%) -"When I am buying my prescription medications, the pharmacist hands me my prescriptions, provides me with thorough medication counseling, and encourages me to ask questions" (34%) -"When I am buying my prescription medications, privacy concerning my prescriptions is maintained by the pharmacist" (35%) -"When I go to the pharmacy with a problem the pharmacist gives me enough time to discuss my problem and listens to me carefully" (37%) -"When I go to the pharmacy to ask any drug-related question, the pharmacist is knowledgeable enough and always ready to answer my questions" (37%)…”
Section: Attitudes Towards Community Pharmacist Rolementioning
confidence: 99%
See 2 more Smart Citations